Coping with Parental Divorce: A Study of Adolescents in A Collectivist Culture of Malaysia - Sumari, Melati; R. Subramaniam, Sarada Devi; Md Khalid, Norfaezah (Taylor & Francis, 2020)
This study uses a phenomenological approach to explore how adolescents cope with parental divorce. A total of 15 participants aged 16 to 17 were selected for the interviews. The participant’s daily activities were monitored for 12 months with the support of social media. Six themes emerged from the collected data: (1) Forgiving of parents; (2) Accepting parental divorce, (3) Maintaining contact with both parents, (4) emotional support from others, (5) Letting it go and moving forward with life, and (6) Appreciating the parent-child relationship. The study provides an insight into the characteristics of adolescents in divorced families, and how they maintain strong, healthy relationships with their parents following a divorce. The study is based on the actual experiences of the participants, and the findings raise awareness about how children are still able to maintain a good relationship with both parents despite the negative impact of parental divorce. The results of the study can also be used as a benchmark by family practitioners on how to help divorced families and promote healthy and functional parent-child relationships. © 2019, © 2019 Taylor & Francis Group, LLC.